Introduction and perspective, historical note - Burnstock, Geoffrey (Frontiers in Cellular Neuroscience, 2013)
P2 nucleotide receptors were proposed to consist of two subfamilies based on pharmacology in 1985, named P2X and P2Y receptors. Later, this was confirmed following cloning of the receptors for nucleotides and studies of transduction mechanisms in the early 1990s. P2X receptors are ion channels and seven subtypes are recognised that form trimeric homomultimers or heteromultimers. P2X receptors are involved in neuromuscular and synaptic neurotransmission and neuromodulation. They are also expressed on many types of non-neuronal cells to mediate smooth muscle contraction, secretion and immune modulation. The emphasis in this review will be on the pathophysiology of P2X receptors and therapeutic potential of P2X receptor agonists and antagonists for neurodegenerative and inflammatory disorders, visceral and neuropathic pain, irritable bowel syndrome, diabetes, kidney failure, bladder incontinence and cancer, as well as disorders if the special senses, airways, skin, cardiovascular and musculoskeletal systems.